LFSR based hybrid pattern scheme achieving low power dissipation and high fault coverage - Islam S.Z.; Ali M.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents a low hardware overhead scan- based test pattern generator (TPG) that can reduce switching activity in circuit under test (CUT) during test and also achieve very high fault coverage with reasonable lengths of test sequences. The proposed TPG is comprised of two TPGs: Seed selected Random Test Pattern Generator (RTPG) and 3-weight Weighted Random Built-in-Self Test (WRBIST). Test pattern generated by seed selected RTPG detect easy-to-detect faults and test pattern generated by 3-weight WRBIST detect hard faults that remain undetected after seed selected RTPG patterns are applied. Experimental results show that the proposed TPG schemes can attain 100% fault coverage for all benchmark circuits with drastically reduced test sequence lengths. This reduction in test sequence length achieved at low hardware cost even for benchmark circuits that have large number of scan inputs. 2008 IEEE.